Review of CCAFS Capacity Enhancement activities - Climate Futures (2014)
CCAFS and the CGIAR research Centers provide cutting-edge research on global climate change, agriculture and food security. CCAFS also has the objective to support Capacity Enhancement (CE) through improvements to: 1. Researchers’ capacity to generate knowledge on climate-smart food systems, adaptive capacity and rural livelihoods under climate change; 2. Decision-makers’ capacity to demand, critique and use this knowledge effectively to work out policy options, and to evaluate and adjust these policy options and related actions; 3. Decision-influencers’ access to information (Climate Futures definition). CE includes the development of skills and knowledge, dissemination of information, education, empowerment and behaviour change. A particular focus is empowerment of underrepresented groups including women. These activities are undertaken across much of the developing world, defined into the regions, East Africa, West Africa, Latin America, Southeast Asia and South Asia (and to a lesser extent the Middle East and North Africa, East Asia, Central Asia and Global). CCAFS has no specific targets for spending or performance on CE, and there is no formal reporting procedure for CE. Reported activities in 2011, 2012 and 2013 include CE outputs, and some reported outcomes and case studies also include CE. CCAFS is scheduled for an external evaluation in 2015 by CGIAR’s Independent Evaluation Arrangement (IEA). As part of the internal preparation for this evaluation, this report provides the findings of an evaluation of CCAFS Capacity Enhancement activities.